The Impact of Coal Quality on Reduction of Environmental Pollution Researched Through Statistical Analysis - Hysen Ahmeti; Ajet Ahmeti; Ragip Behrami (Civil Engineering Journal, 2022)
Today, the region in general but also Kosovo faces a lack of electricity on the one hand and environmental pollution on the other hand from existing power plants where electricity is produced for the community in general in thermo-plants Kosovo A and Kosovo B. The purpose and importance of this paper is that for the samples taken through the layers (floors) of coal by drilling to extract the calorific values of coal (ETU) and the percentage of ash, whose parameters were analysed in the laboratory of geo-mechanics according to the standards (ISO 9001) in order to eliminate the weak part of coal that would have a positive impact on increasing electricity production but also on reducing environmental pollution within the allowed values according to European Union standards. To carry out this work, a large number of drillings were performed from which 91 samples were taken at different depths, these samples were analysed and, at the same time, statistical processing was done in order to find the average caloric value of (ETU) and the content of ash with the lowest value, these parameters will help us to determine the method to be applied during the exploitation in order to create better conditions for the transport process to the power plants by means of conveyor belts and, at the same time raising the quantity of energy production and reduction of carbon dioxide (CO2). Doi: 10.28991/CEJ-2022-08-08-05 Full Text: PDF